Development and thermal modeling of an induction machine - Stephen Ejiofor, Oti; Justin, Ugwu; Damian Benneth, Nnadi; Uche, Ogbuefi (International Journal of Engineering and Technology, 2019)
In induction machines, the major concern is the temperature rise since it determines the maximum loading, in an attempt to avoid insula-tion deterioration and eventual loss of motor life. The effect of excessive heat in the motor stator and rotor windings and the stator mag-netic circuit can degrade the developed performance of the machine and also affect the motor loading and life span if not dispensed properly. This research work examines the thermal model for estimating the stator and rotor temperatures in cage induction motor. A state-variable model of the induction is used. The twin-axis stator reference frame is used to model the motorâ€™s electrical behavior, because physical measurements are made in this reference frame. The thermal model is derived by considering the power dissipation, heat transfer and rate of temperature rise in the stator and rotor. The non-linear equations for electrical behavior of the motor and the thermal state equations for the stator and the rotor are solved using the MATLAB/Simulink blocks. This is to give room for the determination of the temperature of the stator and rotor windings inside the induction machine so as to evaluate the thermal stability of the induction motor and to check whether the insulation of the copper windings is sufficient at different operating conditions. It was found out from the thermal model analysis that the temperature of the stator and rotor windings increases due to stator and rotor copper losses which depend on the stator current. As the stator current is increased by increasing the torque, the temperature of each element is consequentially made to increase.Â Â